The Conception of the Three Modes of Consciousness (Trisvabhāva) in the Texts of Early Yogācāra Buddhism - Beinorius, Audrius (Acta Orientalia Vilnensia, 2000)
Author deals with the problem of consciousness in Yogācāra Buddhism analysing the early Sanskrit texts of the founders of this school: Maitreyanātha, Asaga, Vasubandhu and Sthiramati. According to the central notion of Yogācāra, everything experienceable is “ideation–only” (vijñapti–mātra), things exist only as processes of knowing, not as “objects” and outside the knowing process they have no reality. This process is explained with the help of the concept of the “store–consciousness” (ālaya–vijñāna), which is the conditional ground for all the seven other consciousness and storehouse of all previous impressions (vāsanās), seeds (bījas), which produce mental phenomena. The Yogācāras analyses the nature of thing conceived by the human consciousness into three modes (trisvabhāva): conceptualized (parikalpa), dependent (paratantra) and perfect (parinipanna). The conceptualized phenomena are mere imagination, false conceptions (vikalpa) and is of non–real existence. The dependent phenomena arise in dependence upon and interaction with other factors of mind. It is the product of dependent causation and mixture of pure and defiles aspects. The perfect nature is the true or ultimate nature, which is non–dual Emptiness (śūnyatā) itself, also known as “Suchness” (tathatā) and the reality is known “as it is” (yathā bhūta).According to the Yogācāras it is possible to free consciousness from latent impresions, when the store consciousness undergoes the process of the devolvment that is called “a revoliution at the basis” (āśray parāvr̥tti, gnas yons–su–gyur–ba). The unpure dhramas belongs to the conceptualized mode of consciouseness (parikalpita), pure dharmas – to the perfect one (parinipanna). So “revoliution at the basis” is nothing else as elimination from the store–consciousness the unpure dharmas, activization the pure ones and the transforming the conceptualized nature of consciousness into the perfect (nirvḁ̄a). The path to liberation according to Yogācāras is the process of transformation divided into five stages – sambhārā mārga, prayogā mārga, darśana mārga, bhūvanā mārga, niha mārga, and consist in elimination of the all gnoseological (jñeya avarḁa) and psychological defilements (kleśa āvarḁa) of store–consciousness.